D-type optical fiber immunoglobulin G sensor based on surface plasmon resonance. (November 2020) - Chen, Mengdan; Lang, Tingting; Cao, Bobo; Yu, Yuzhen; Shen, Changyu
Highlights: Most current biological measurement methods require bulky and expensive equipment. A D-type optical fiber biosensor based on surface plasmon resonance is proposed. This sensor has a simple structure and is easy to make. The fabricated biosensor exhibits high sensitivity to human immunoglobulin G. Abstract: In this paper, we report a D-type optical fiber biosensor for human immunoglobulin G (HIgG) detection based on surface plasmon resonance (SPR). The SPR phenomenon was both simulated by COMSOL and observed experimentally. To fabricate the sensor, the cladding of a multimode optical fiber (MMF) was polished using a grinding wheel to obtain a D-type cross-section. Next, a gold film was sputtered on the surface of the MMF. The optimal gold layer thickness and grinding depth were determined through simulations. As per the experimental results, the optimized sensor exhibited high refractive index (RI) sensitivity, which ranged from 1590.9 nm/RIU to 3513.3 nm/RIU for RI values of 1.343 to 1.373. Subsequently, Poly dimethyl diallyl ammonium chloride (PDDA) and Poly(sodium-p-styrenesulfonate) (PSS) were deposited four times in sequence to form polyelectrolyte self-assembled multilayers for the surface functionalization of the fiber. HIgG and goat anti-HIgG (GaHIgG) were chosen as the bioconjugate pair for evaluating the functionality of the fabricated biosensor, and the sensitivity to IgG was determined to be 91 nm/(mg/ml). The specificity of the biosensor was also verified through comparison tests performed using gelatin, horse IgG, and swine IgG. The obtained results confirmed the suitability of the biosensor for use in various biochemical applications.